MODEL PENGEMBANGAN DAN EVALUASI PEMBELAJARAN BAHASA INDONESIA DI MTs KARANGKAJEN - Amalia Resti Pamuji; Dian Hidayati (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study describes the development and evaluation model of learning in Indonesian language lessons at MTs Karangkajen. The research objective was to determine the model of development and evaluation of learning to improve the quality of students towards Indonesian language lessons. This type of research uses descriptive qualitative research. Methods of data collection using interviews, observation and documentation. Data analysis with three stages: reduction, presentation of data and concluding. The research results found 1) the Indonesian language learning development model at MTs Karangkajen using the reading, listening, writing and speaking learning model, 2) the evaluation of the Indonesian language learning model at MTs Karangkajen was carried out based on daily tests, midterm tests, quizzes fast, as well as the results of discussions and questions and answers to students. The school principal conducts class visits and reports on learning outcomes at the end of the semester by the teacher as an evaluation of learning to increase student ability and achievement in Indonesian.